Forest Governance 2.0 : A Primer on ICTs and Governance - Castrén, Tuukka (World Bank, Washington, DC, 2014)
In this report, the authors study the experiences and lessons learned on the use of Information and Communication Technology (ICT) to promote good forest governance, and identify ways modern technology can be applied to meet the challenges of improving forest governance and achieving sustainable forest management. The authors believe that countries and their development partners can make their forest governance reforms more effective and inclusive through the use of information management and technology. The main focus in the report is on institutions how they interact with stakeholders and how their performance can be strengthened. The authors are trying to fill the gap in which experiences from various forest governance pilots are not widely shared. They do not cover forest inventories or technical resource assessment; extensive literature on these topics is available from various national and international research institutions and the UN Food and Agriculture Organization (FAO). They do not present all possibilities and current uses of ICT in forest governance. Their goal is to demonstrate the range and diversity of approaches, and the feasibility of using technology to promote forest governance. The report covers both 'small' and 'big' ICT. Small and more affordable ICT applications are often based on consumer devices for which the underlying technology is available ready-made from commercial sources. These devices can be used to interact with the public and in professional applications. The big ICT dimension includes professional applications that are tailor-made and often system-based and expensive. The report does not try to provide solutions for specific problems, but it demonstrates the extent to which information management is an essential part of sector reform. Development professionals dealing with forest governance can use their findings in consultations with partner countries and to help plan interventions. The report begins with a discussion of recent developments in the governance discourse to set the stage and show how the definition of forest governance has evolved. The authors then describe recent developments in access to ICT services, particularly in rural areas, and how information is used in the forest sector. There has been much concern about in-country digital divides; while they still exist, the past few years have seen an unprecedented increase in access to technology in rural areas.